Hubungan Self-Efficacy dengan Kemampuan Pemecahan Masalah Matematis Siswa SMA - Relifa G Wiranagari; Sudianto Sudianto (Program Studi Pendidikan Matematika, Universitas Majalengka, 2025)
This study aims to explore the relationship between self-efficacy and upper secondary school students’ mathematical problem-solving abilities. Self-efficacy plays a critical role in shaping students’ confidence and perseverance when facing challenges in mathematics learning. The study adopted a mixed methods approach with an embedded design, prioritizing quantitative analysis supported by qualitative insights. Data were collected through a self-efficacy questionnaire and a mathematical problem-solving test based on Polya’s stages. The results revealed a significant positive relationship between self-efficacy and students’ mathematical problem-solving skills. These findings suggest that students with higher self-efficacy tend to perform better in solving mathematical problems. Strengthening self-efficacy should therefore be an integral part of mathematics teaching strategies at the upper secondary school level.